Effect of Steam and Bleaching Treatment on the Characteristics of Pineapple Leaves Fibre Derived Cellulose - Surenthiran, Gnanasekaran; Siti Nur Najihah, Muslih; Jun Haslinda, Haji Shariffuddin; Noor Ida Amalina, Ahamad Nordin (Universiti Putra Malaysia, 2020)
Pineapple leaf fibres (PALF) is one of the abundant residues generated from pineapple plantation. The residues are left on the plantation for nutrient cycling or burning, and this circumstance leads to environmental issues. PALF has high cellulose content among other natural fibres. Cellulose is a reinforcing element that exists as whisker-like microfibrils and has a long-chain structure. In this study, cellulose produced from PALF was treated by steam and chemical treatment. The fibre was treated with steam at 121°C, a pressure of 21 psi for 30 or 60 min. Next, the steam-treated fibre was treated with 5 wt% sodium chlorite (NaClO2) solution with pH adjusted between 4 and 5 for 90 min. The condition was varied with three different temperatures, which were room temperature, 50, and 70°C. Then, the bleached fibre was treated with 5 wt% sodium hydroxide (NaOH) at room temperature for 3 h. After the treatments, the fibre was analysed for its thermal stability, morphology, and chemical composition. Cellulose obtained from the treatment condition of steam for 60 min, bleaching at 70°C, and alkali treatment at room temperature expressed the highest degradation temperature of 276°C at 20% weight loss, percentage of cellulose of 86% and lowest moisture content (8%) compared to others sample. It also had an excellent surface morphology with finest fibril disintegration. It showed longer steam treatment (60 min) degrading more hemicellulose; and bleaching treatment at high temperature (70°C), increasing the rate of oxidative delignification. In conclusion, the suggested treatment provides a simple but efficient method to isolate cellulose that can be used for various types of applications.